2019
DOI: 10.3892/etm.2019.7853
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‑21 suppresses 1‑methyl‑4‑phenylpyridinium‑induced neuronal damage in MES23.5 cells

Abstract: Accumulating evidence suggests that overproduction of oxidative stress, increases neuroinflammation and activates apoptosis. These two processes are associated with the development of Parkinson's disease (PD). The present study aimed to investigate the role of miR-21 in the development of PD. 1-Methyl-4-phenylpyridinium (MPP + ) was used to induce a PD-like model in MES23.5 cells. The results of the reverse transcription-quantitative PCR assays indicated that miR-21 levels were markedly increased in MES23.5 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, miR-21 could prevent human neural stem cell injury induced by oxygen and glucose deprivation through PDCD4/caspase-3 pathway [33,34]. In contrast, miR-21 over-expression was associated with right ventricle dysfunction in patients with hypoxia-induced pulmonary hypertension, and promoted neuronal damage in vitro [26,35]. In the present study, we found decreased miR-21-5p gene expressions both in severe OSA patients and in response to IHR stimuli.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, miR-21 could prevent human neural stem cell injury induced by oxygen and glucose deprivation through PDCD4/caspase-3 pathway [33,34]. In contrast, miR-21 over-expression was associated with right ventricle dysfunction in patients with hypoxia-induced pulmonary hypertension, and promoted neuronal damage in vitro [26,35]. In the present study, we found decreased miR-21-5p gene expressions both in severe OSA patients and in response to IHR stimuli.…”
Section: Discussionmentioning
confidence: 52%
“…In addition, miR-7 downregulated RelA, a member of the nuclear factor κB (NF-κB) family of transcription factors, and augmented neuronal glucose transporter 3 (Glut3) to promote glycolysis in SH-SY5Y cells and ReNcell VM cells [ 34 ]. Mao et al, found that miR-21 downregulation was able to attenuate MPP + -induced MES23.5 cell death by apoptosis inhibition and reactive oxygen species (ROS) scavenging [ 35 ]. In SH-SY5Y cells and primary dopaminergic neurons, astrocyte-derived exosomal miR-200a-3p downregulated MKK4 (mitogen-activated protein kinase kinase 4) and prevented MPP + -induced apoptotic cell death [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-21 levels were markedly increased in MES cells following 1-methyl-4-phenylpyridinium (MPP + ) treatment. Downregulation of miR-21 could reduce the MPP + -mediated cytotoxicity via inhibition of apoptosis and inflammatory responses in MES cells, which provides a novel approach to PD treatment (Mao and Ding, 2019). Su et al (2016) showed that the level of miR-21 was significantly increased in PD cells and mouse models.…”
Section: Parkinson's Diseasementioning
confidence: 99%